Development of Brown Seed and Release of “Biradama” Tef Variety for Potential Areas of Amhara Region and Beyond - Ferede, Misganaw; Tariku, Sewagegn; Fentahun, Atalay; Fentahun, Atinkut; Misganaw, Gedefaw; Dagnaw, Zigale; Getaneh, Desalegn; Wale, Sefinew; Degenet, Yismaw; Chakle, Shumet; Taye, Yasin (Department of Agronomy and Horticulture, IPB University, 2024)
Brown seed tef variety development did not get much attention as white seed in tef improvement program in Ethiopia. However, brown seed tef is locally demanded for home consumption and foreign markets. It has wider genetic variability that can be exploited in tef improvement program. Therefore, the study was conducted to develop high yielding brown seed tef variety with desirable agronomic and quality traits. Eighteen tef genotypes with standard and local checks were used for this study. The study was conducted at Adet (2019 and 2020), Mota (2019 and 2020), Takusa (2019 and 2020) and Finote Selam (2020) in Amhara region with a total of seven environments. A randomized complete block design with 3 replications was used in this experiment. The analysis of variances showed significant differences for the evaluated traits in genotypes, environments and genotypes by environment interaction. The genotype Accession # 236756-3 is a stable genotype than theother tested genotypes. The grain and straw yield performance of the genotype accession # 236756-3 was 2529 kg.ha-1 and 6040 kg.ha-1, respectively. It had 14.3% and 25.2% grain yield advantage over standard check “Filagot”, and the farmer’s variety, respectively. In addition, it had 13.6% and 19.4 % straw yield advantage over “Filagot” (standard check) and the farmer’s variety, respectively. A variety verification trial of the genotype accession # 236756-3 was conducted in test locations with a standard check (“Filagot”) and the farmer’s variety. The field performance of the verification trial was evaluated by National Technical Committee and released the variety for large production in tef production potential areas of Amhara Region and similar agro-ecologies of Ethiopia with a local name ‘Biradama”. This newly released variety can be used as parental material in the genetic improvements of tef.